2013
DOI: 10.1177/1071100713475357
|View full text |Cite
|
Sign up to set email alerts
|

Declines in Lower Extremity Amputation in the US Medicare Population, 2000-2010

Abstract: Level III, retrospective comparative database analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…Over 8% of the population has diabetes, disproportionally leading to nearly two thirds of all non-traumatic amputations (nearly 66,000 in 2006) (CDCP, 2011). Recently, there has been a trend of reduced non-traumatic amputation rates, both in veterans (Tseng et al, 2011) and the general population (Belatti and Phisitkul, 2013; Li et al, 2012), likely a result of improved preventative care, increase revascular interventions, and evolving orthopaedic management (Belatti and Phisitkul, 2013). However, in terms of the shear number of amputations per year (Belatti and Phisitkul, 2013; Tseng et al, 2011), and by the fact diabetic subjects undergo a disproportionate percentage of all amputations (CDCP, 2011; Li et al, 2012), diabetic foot ulceration remains an issue that requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Over 8% of the population has diabetes, disproportionally leading to nearly two thirds of all non-traumatic amputations (nearly 66,000 in 2006) (CDCP, 2011). Recently, there has been a trend of reduced non-traumatic amputation rates, both in veterans (Tseng et al, 2011) and the general population (Belatti and Phisitkul, 2013; Li et al, 2012), likely a result of improved preventative care, increase revascular interventions, and evolving orthopaedic management (Belatti and Phisitkul, 2013). However, in terms of the shear number of amputations per year (Belatti and Phisitkul, 2013; Tseng et al, 2011), and by the fact diabetic subjects undergo a disproportionate percentage of all amputations (CDCP, 2011; Li et al, 2012), diabetic foot ulceration remains an issue that requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…5 The observed downturn in the age-adjusted LLA incidence rates is consistent with the recent literature. [6][7][8] In the US, the rates were reported to have declined from 2000 to 2010. 6 It is difficult to meaningfully compare the rates across countries because different methods have been employed for reporting the incidence rates.…”
Section: Lower Limb Amputation In Canadamentioning
confidence: 99%
“…5 Unlike earlier studies that have shown an increase in the incidence of LLA in Western countries, 6 the most recent studies have reported a decline or no change in the rates. [7][8][9] The LLA incidence data are unknown for Canada. As a result, incidence rates from other countries, particularly the United States, are commonly used to support health care planning and research initiatives.…”
mentioning
confidence: 99%
“…1 The number of patients with DPN has increased in recent years while the numbers of patients with ulcers, peripheral arterial disease, and lower extremity amputation have decreased. 2,3 Although the reason for improvements isn't known, it' s likely to be a combination of better preventive foot care, intensive blood glucose management, and improved therapies for foot ulcers.…”
Section: Understanding Dpnmentioning
confidence: 99%